Century 21 Plus - Hoggatt, Jack
CENTURY 21 PLUS, COMPUTER APPLICATIONS WITH DOCUMENT FORMATTING Formatting is an alternative starting point for any keyboarding or computer applications course where students have already had new-key instruction. This new text is targeted for students who have had keyboarding and some basic computer applications instruction in another course